2013
DOI: 10.4028/www.scientific.net/amr.756-759.4394
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Automation to Maritime Technology

Abstract: Due to incredibly advancing technology and reduced manning levels in the maritime industry there is now a cultural shift in the maritime industry toward increased levels of automation in tasks, particularly with regard to navigation systems. But there are two sides to the automation advances. Increasing automation causes the loss of situation awareness, which can significantly affect performance in abnormal, time-critical circumstances. This paper presents an overview of the application of automation in marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Consequently, seafarers are frequently required to familiarize themselves with the technologies and devices of every vessel they join, which they may not have used before, shortly after embarkation. This must be done promptly while also becoming familiar with or refreshing their knowledge of corporate regulations and procedures [58]. Moreover, operating manuals are often lengthy and occasionally created without a thorough understanding of user requirements, making it challenging to identify essential instructions quickly.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, seafarers are frequently required to familiarize themselves with the technologies and devices of every vessel they join, which they may not have used before, shortly after embarkation. This must be done promptly while also becoming familiar with or refreshing their knowledge of corporate regulations and procedures [58]. Moreover, operating manuals are often lengthy and occasionally created without a thorough understanding of user requirements, making it challenging to identify essential instructions quickly.…”
Section: Othersmentioning
confidence: 99%
“…The study demonstrated that each human error played a crucial role in the occurrence of disasters, indicating that the accident could have been averted if any faults in the chain of events had been avoided. Therefore, the primary challenge in improving maritime safety lies in understanding the role of the human factor [58]. The literature emphasizes the need for methods spanning both physical and virtual environments to enhance the expertise of maritime teams, particularly focusing on the youth entering the field, to reduce human errors arising from a lack of familiarity with processes and contexts, a major contributor to maritime incidents [65].…”
Section: Improvement and Preventionmentioning
confidence: 99%
“…Moreover, studies have shown that the increasing of the workload levels have prompted several auxiliary impacts. For example, exhaustion and the lack of situational mindfulness, both of which have been appeared to be significant reasons for causing accidents at sea [5,6]. In [7], it is stated that the advancement of automation on-board do not reduce the workload of the crew.…”
Section: A Workloadmentioning
confidence: 99%